Characterization of metabolites in rats after intravenous administration of salvianolic acid for injection by ultra‐performance liquid chromatography coupled with quadrupole‐time‐of‐flight mass spectrometry. (14th March 2016) - Miao, Jingzhuo; Sun, Wanyang; Huang, Jingyi; Liu, Xiaolin; Li, Shuming; Han, Xiaoping; Tong, Ling; Sun, Guoxiang
Abstract: It is an essential requirement to clarify the metabolites of traditional Chinese medicine (TCM) injections, which contain numerous ingredients, to assess their safe and effective use in clinic. Salvianolic acid for injection (SAFI), made from hydrophilic phenolic acids in Salvia miltiorrhiza Bunge, has been widely used for the treatment of cerebrovascular diseases, but information on its metabolites in vivo is still lacking. In the present study, we aimed to holistically characterize the metabolites of the main active ingredients in rat plasma, bile, urine and feces following intravenous administration of SAFI. An ultra‐performance liquid chromatography coupled with quadrupole‐time‐of‐flight mass spectrometry (UPLC/Q‐TOF‐MS) method was developed. Combining information on retention behaviors, multistage mass spectra and literature data, a total of eight prototypes and 52 metabolites were tentatively characterized. Metabolites originated from rosmarinic acid and salvianolic acid B comprised the majority of identified compounds. Meanwhile, four metabolites derived from salvianolic acid D and five from salvianolic acid B are reported for the first time. This study revealed that methylation, sulfation and glucuronidation were the major metabolic pathways of phenolic acids in SAFI in vivo . Furthermore, the developed UPLC/Q‐TOF‐MS method could also benefit the metabolic investigation of extracts and preparations in TCM with hydrophilic ingredients. Copyright © 2016 John Wiley & Sons, Ltd.